Análisis multicriterio en la evaluación del impacto social de presas - Campuzano Salazar, Amaya Julieta (My University, 2007)
Análisis multicriterio en la evaluación del impacto social de presas
Keywords: Análisis multicriterio en la evaluación del impacto social de presas